2023
DOI: 10.1083/jcb.202303097
|View full text |Cite
|
Sign up to set email alerts
|

GPI anchors: Regulated as needed

Abstract: GPI anchoring is an essential post-translational modification in eukaryotes that links proteins to the plasma membrane. In this issue, Liu et al. (2023. J. Cell Biol.https://doi.org/10.1083/jcb.202208159) suggest, for the first time, a regulation on demand of the GPI glycolipid precursor biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Studies indicated a crucial role of GPI-TA in regulating glycolipid biosynthesis, since GPI biosynthesis is suppressed by the ER-associated degradation pathway when cells are defective in transferring the complete GPI core to proteins to prevent GPI accumulation ( 9 , 45 ). Biosynthesis of GPI is upregulated in ER-associated degradation-deficient cells ( 46 ).…”
Section: Key Roles Of Pigm Pigx ...mentioning
confidence: 99%
“…Studies indicated a crucial role of GPI-TA in regulating glycolipid biosynthesis, since GPI biosynthesis is suppressed by the ER-associated degradation pathway when cells are defective in transferring the complete GPI core to proteins to prevent GPI accumulation ( 9 , 45 ). Biosynthesis of GPI is upregulated in ER-associated degradation-deficient cells ( 46 ).…”
Section: Key Roles Of Pigm Pigx ...mentioning
confidence: 99%
“…Because of its role in the conserved post-transcription modification processes, cell surface glycosylphosphatidylinositol-anchoring technology is expected to aid the construction of novel functional yeast cells with oriented protein transportation and accurate colocalization. Their construction depends on the functional proteins that reside on the plasma membrane ( Inokuma et al, 2021 ; Aguilera-Romero and Muñiz, 2023 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%